E-Promotion Techniques for Make-Up Artist Services Via Instagram (Tyzaptan Study in Rantepao, North Toraja) - Boroallo, Sakty; Dendang, Silvani Majid; Kamaruddin, Syamsu A. (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to analyze the e-promotion techniques carried out by Tyzaptan via Instagram. . The research method used is qualitative research with a content analysis approach and the main data source in this research is Instagram. The findings in this research are that the promotional techniques used by Tyzaptan are social media techniques, especially Instagram. This social media technique contains advertising, publicity and sales promotions for the services or goods offered. Promotion is carried out by displaying a portfolio of services that have been provided on their Instagram account.